Over de schreef : christendom en humanisme, communisme en democratie - Delfgaauw, Bernard (Bernardus Maria Ignatius), 1912-1993 (Baarn : Het Wereldvenster, 1964)
Philosophical essay on christianity, religion and politics, e.g. concerning war and peace, democracy and communism.
Theory